Specifying the Primary and Secondary Standards that Affect Contracts Between Public and Private Sectors in the Power Plants and their Weights - جراد, فايز; جنود, علي; رحابي, محمد (Latakia University Journal -Engineering Sciences Series, 2022)
In Syria, the power plants sustained heavy damage that affected the economy badly, turning the country from an exporter of electricity to one that can barely secure its need. Therefore, investing in building power plants will lead to growth and development, which is clearly visible in the economic part. Since the government sectors are unable to provide these investments, we turned to the private sector to invest in this field in a way that interests both parties. In this case study, 6 primary standards that affects contracts between public and private sectors and were ranked based on their importance. First, the political standard, then legal, social, economic, technical, and finally, environmental. There were also 45 secondary standards which directly include all parties, that affect building power plants as well. These secondary standards were categorized based on their importance from highly important- all parties committing to the contracts- to the lesser important-the role that the Ministry of Affairs and Labors in giving work permissions to foreign labors. All of this is based on previous studies, interviews with decision-makers, and related questionnaires